Atratividade turística, imagem, reputação e recomendação on-line: um modelo integrativo das percepções de turistas de Ouro Preto - Mariana de Freitas Coelho (2013)
The competitiveness among touristic destinations have urged academic interest in researching the factors which contribute for the destinations’ choice. In one hand, researchers focus on establishing the factors which impact on the tourist perception of the destination. Other approach tend to decompose touristic attractiveness in order to find its most important dimensions. However, a few studies have associated destination attractiveness with future behavior. This research aims to find the relation between the attractiveness factors of a touristic destination perceived by its consumers and their intention to recommend the destination in on-line media. The city of Ouro Preto, Minas Gerais, Brazil, was chosen as to develop the research, due to its touristic relevance in a national and regional context. The adopted method consisted in an exploratory-descriptive research, with a mixed approach. Firstly, a two-step qualitative phase interviewed 12 local stakeholders to understand the phenomenon holistically. Then, 15 experts helped on understanding the concept of reputation in touristic destinations. Secondly, a quantitative research surveyed 396 tourists visiting Ouro Preto, over 18 years old. The qualitative phase showed that potential attractions and destination’s competitors should also be taken into account in attractiveness studies. Also, the 4 main themes for destination reputation where communication, assessment, distinction and time. The quantitative research model has not confirmed the hypotheses based on Das et al. (2007), which related factors impacting on tourist attractiveness (Accessibility, Infrastructure, Destination’s Atmosphere, Distinctive Local Features, Perceived Environment and Culture) and Perceived Attractiveness. Therefore, an alternative model with the other approach of attractiveness’ researches was tested. Through an exploratory factor analysis 5 dimensions of attractiveness were found: Infrastructure, Touristic Resources, Perceived Environment, Distinctive Atmosphere and Museum’s Atmosphere. These dimensions were all impacted by the tourist’s perceived attractiveness. Finally, the study attests that there is, at least in the context of this research, both a relationship between reputation and perceived attractiveness, and perceived attractiveness and intention to recommend the destination on the internet.